Hydrophobization of limestone from the deposit 'Cancar' Aranđelovac using stearic acid - Mihajlović Slavica R.; Sekulić Živko T.; Radulović Dragan S.; Stevanović Dejan R.; Kašić Vladan D. (Tehnika, 2015)
The paper presents the results of investigation of the possibility of hydrophobization of calcite from deposit 'Cancar' company 'Good stone' - Aranđelovac, Serbia. Hydrophobization of calcite surface is performed with stearic acid, and the sample which is used is a product made from the 'Good stone' mean grain diameter 29,14μm. The concentration of stearic acid in the experiment, were as follows: 0.3; 0.5; 0.8; 0.9, 1; 2, 2.5, 3 and 4%. Results showed that the hydrophobization degree of coating increases with increasing concentration of the stearic acid used for modifying. This indicates that was not changed orientation of the hydrocarbon chains in the adsorbed layer with increasing concentrations of stearic acid available for adsorption. Adsorption was always such that the molecules of stearic acid kept the orientation of its hydrophobic portion (the hydrocarbon chains) opposite to surface of the calcite. As the degree of coating can be taken as a measure of hydrophobicity of the obtained products, results suggest that complete hydrophobicity of the surface of calcite occurs at a concentration of 3%.